Research on the Characteristics of Open winding Brushless DC Motor - Qi, Huang; Ling, Luo; Li-kun, Xue; Yang, Tang (International Conference on Electrical Machines and Systems (Online), 2019)
Brushless DC motor (BLDCM) is widely used in electrical drives application. But the neuter port in Y connected BLDCM windings could leads to torque ripple and low reliability. Open winding BLDCM system has no neuter port of phase windings whose voltages and currents could be controlled separately. The topology and eight kinds of conduction models of open winding BLDCM system are introduced. The electromagnetic foundation of open winding BLDCM is analyzed. Then a mathematical model of the open winding BLDC drive system is simulated by MATLAB SIMULINK. A prototype of open winding BLDCM and test system is designed. Experimental results show that, compared to Y connected BLDCM, open winding BLDCM has a wider speed regulation range and less commutation torque ripple, the torque-speed characteristic of them are similar.